(AL-MAWAD AT-TA’LIMIYAH LI MAWAD AL-BALAGHAH ALA ASASI AL-AYAT AL-QUR’ANIYAH) - Syarifuddin; Burhanudin (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2019)
Teaching material is one of teachers’ resources. Koran is complete teaching material for Islamic or Arabic knowledge including Ma’ani; one of three parts from Balaghah. Surah al-Hadid is one of surahs in Koran. It contains examples of Ma’ani. This article (research) is library research. This research used descriptive method. Research data is all verses of surah Hadid. The result of this research is that in surah al-Hadid there are 151 examples of kalamkhabar, 16 kalaminsya’, 38 examples of washl, 21 examples of fashl, 12 examples ijaz, four examples of ithnab and 24 examples of qashr.